Insect Science-Diversity, Conservation and Nutrition 2018
DOI: 10.5772/intechopen.74223
|View full text |Cite
|
Sign up to set email alerts
|

Development of Beekeeping: An Analysis Using the Technique of Principal Components

Abstract: Beekeeping is an economic activity of the Brazilian agricultural sector and a powerful tool to achieve sustainable development. However, beekeeping still remains a modest activity compared to other areas, with a lack of technical knowledge and beekeeping practices that need to be standardized. This study represents a proposal for the diagnosis of beekeeping, to facilitate decision-making and to provide a faster development of the beekeeping activity. We investigated the process of adoption of beekeeping practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The diastase activity values reported ranged from 11.14° to 22.69° Göthe for Brazilian honey. Diastase activity of honey ranged from 6.02° to 21.99° Göthe [ 176 ]. Kamal et al [ 177 ] reported values of diastase activity ranging from 12.63° to 16.33° Göthe for five honey samples harvested from Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…The diastase activity values reported ranged from 11.14° to 22.69° Göthe for Brazilian honey. Diastase activity of honey ranged from 6.02° to 21.99° Göthe [ 176 ]. Kamal et al [ 177 ] reported values of diastase activity ranging from 12.63° to 16.33° Göthe for five honey samples harvested from Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…In the research done by Udofia and Edet (2016) at Ethiopia, the proportion of adopting the modern beekeeping techniques by beekeepers is found quite low and it is determined that only 16.80% of the beekeepers adopt modern beekeeping techniques. According to the research done by Chambo et al (2018), more than half of the beekeepers adopt more than 74% of the suggestions about the harvest and after harvest. According to the research done by Kumar (2013), farmers adopt 45.71% of the innovations about bee feeding and 36.66% of the innovations about migratory beekeeping.…”
Section: Discussionmentioning
confidence: 99%